2016
DOI: 10.1016/j.joco.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin in ophthalmology: A literature review

Abstract: PurposeTo review the current literature on ocular application of erythropoietin (EPO).MethodsA comprehensive search was performed on Pubmed and Scopus databases. All selected articles were reviewed thoroughly by the authors to review current applications of the EPO in ocular diseases.ResultsVarious aspects of administration of EPO for different ischemic, traumatic, vascular, and degenerative disorders have been explained. The articles are generally preclinical with few small studies reporting clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…Recently, EPO has revealed neuroprotective properties on the retina in addition to its hematopoietic effect [11,26]. Several investigations have addressed EPO properties to mediate protection against retinal damage through different pathways, including increasing resistance to inflammation, oxide-induced damage, ischemia, degeneration, and permeability [13,27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EPO has revealed neuroprotective properties on the retina in addition to its hematopoietic effect [11,26]. Several investigations have addressed EPO properties to mediate protection against retinal damage through different pathways, including increasing resistance to inflammation, oxide-induced damage, ischemia, degeneration, and permeability [13,27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that erythropoietin inserted exogenously contributes to the preservation of the external blood-retinal barrier, acting on processes at the level of the retinal pigment epithelium. In addition, intravitreal injections of rhEpo have led to the inhibition of VEGF and stabilization of the function of the blood-retinal barrier, and also to a shortterm positive effect on the chronic macular edema that has until then been practically refractory to any potential therapy (43).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of erythropoietin receptors in the retinal layers indicated possible developmental, physiologic, and therapeutic roles of erythropoietin in the eye. [30,31] The erythropoietin seems to have protective effects on the eye and play roles in the biological pathway of many ocular disorders such as diabetic retinopathy, retinopathy of prematurity, glaucoma, age-related MD, optic neuritis, and retinal detachment. [3234] Recently, the relationship between advanced CKD patients, especially dialysis patients, and MD has been reported using similar national database.…”
Section: Discussionmentioning
confidence: 99%